Cases on technologies for educational leadership and administration in higher education - Luppicini, Rocci (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012., 2017)
electronic texts (538 p.) : digital files.